2009
DOI: 10.1002/adfm.200801122
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photophysical, and Electroluminescent Device Properties of Zn(II)‐Chelated Complexes Based on Functionalized Benzothiazole Derivatives

Abstract: New Zn(II)‐chelated complexes based on benzothiazole derivatives, including substituted functional groups such as methyl (MeZn), methoxy (MeOZn), or fluorenyl unit (FuZn), are investigated to produce white‐light emission. 2‐(2‐Hydroxyphenyl)benzothiazole derivatives in toluene and DMSO exhibit excited‐state intramolecular proton transfer (ESIPT), leading to a large Stokes shift of the fluorescence emission. However, in methanol they exhibit no ESIPT due to the intermolecular hydrogen bonding between the 2‐(2‐h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 39 publications
(25 reference statements)
0
23
0
Order By: Relevance
“…The fluorinated complex might be more soluble because of the enhanced intermolecular repulsion, while the luminescence characteristics are also affected, for instance, by the substitution of high‐frequency C–H vibrations with low‐frequency C–F vibrations, which results in reduced quenching , . Likewise, Roh and co‐workers observed that the near‐IR emission of erbium pentafluorobenzoate increased 1.5‐fold relative to that of erbium benzoate. Ye and co‐workers proved that the fluorination of the organic ligand leads to the increase of the luminescence efficiency, as reflected in the values of Judd–Ofelt parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorinated complex might be more soluble because of the enhanced intermolecular repulsion, while the luminescence characteristics are also affected, for instance, by the substitution of high‐frequency C–H vibrations with low‐frequency C–F vibrations, which results in reduced quenching , . Likewise, Roh and co‐workers observed that the near‐IR emission of erbium pentafluorobenzoate increased 1.5‐fold relative to that of erbium benzoate. Ye and co‐workers proved that the fluorination of the organic ligand leads to the increase of the luminescence efficiency, as reflected in the values of Judd–Ofelt parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, fluorescent zinc(II) complexes have been widely studied for chemical sensing, bio‐imaging, and optoelectronic device applications . The archetypal luminescent Zn II complexes are usually supported by 2‐hydroxylphenylbenzothiazole (BTZ), bis‐dipyrrinato, and Schiff base ligands . In comparison with the low‐to‐moderate yields in syntheses of organometallic emitters, which usually require harsh reaction conditions, syntheses of these Zn II complexes can be performed under very mild conditions in high yields because of the facile coordination of phenolate and imine ligands to the Zn II ion.…”
Section: Introductionmentioning
confidence: 99%
“…We have chosen fluorescent benzothiazole derivatives as they are good candidates for the functionalization of nanoparticles because of their biocompatibility. For example, the photophysical, photochemical, and biological properties of 2-(2-hydroxyphenyl)benzothiazole ( hpbtz ) have been studied as antitumor, anti-inflammatory, and as positron-emission tomography (PET) imaging in the diagnosis of Alzheimer’s disease [ 21 , 22 , 23 ], and there are a good number of reports on reactive probes based on the hpbtz moiety for the selective detection of different analytes, such as Zn 2+ ion [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, several probes are prepared under harsh conditions or by using multi-step procedures [ 31 , 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%